An Implementation to Determine the KKM of Music Subject at Junior High School - Utami, Mutiara Arlisyah Putri; Syamsuddin, Syaiful (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
A KKM determination is the initial stage of assessment. However, there are still some issues related to the topic, especially in musical some issues related to the topic, especially in music. Therefore, this research used a discrepancy evaluation model to describe the purpose of (1) the implementation level of KKM determination in music, specifically in terms of intake, complexity and carrying capacity. (2) The teachers’ constraints in determining KKM There were six music and art teachers from a junior high school who were taken as subjects in this research. Those subjects were selected using purposive sampling. Data were collected through interviews, documentation, and observations. Data analysis used qualitative analysis and descriptive statistics supported by quantitative data. The results showed that the implementation level of KKM determination in terms of technical procedures was categorized as